RETRO-AORTIC LEFT RENAL VEIN WITH DOUBLE LEFT RENAL ARTERY: A CASE REPORT - K., Vishal; V., Vinay K.; K., Remya; Swathi (Journal of Health and Allied Sciences NU, 2014)
The kidneys are the excretory organs. The kidneys are supplied by right and left renal arteries at the level of second lumbar vertebrae. They are drained by right and left renal vein which runs anterior to renal arteries.During routine dissection of an adult male cadaver in the department of Anatomy, we observed an unusual variation in the blood vessels supplying left kidney.These variations are due to persistence of embryonic vessels.Though variations in the renal vessels are common, proper knowledge of variations is essential not only to the anatomists but also for the clinicians and to perform surgical and radiological procedures more safely and efficiently.
Keywords: Kidney; Renal artery; Renal vein